The identification of cooked grain elongation trait in rice using molecular markers - Nguyen, Thanh Binh (2016)
Cooked grain elongation (CGE) is a very important trait for determining the quality of cooking and eating in rice. The present study was carried out to evaluate the efficacy of molecular markers and integration of conventional method with these markers for the detection of CGE trait in different rice genotype. Ten simple sequence repeats (SSR) markers and a single nucleotide polymorphism (SNP) marker system of EFP/ERP/IRSP/IFLP primers were used to identify the CGE trait in twenty rice varieties. The conventional method was processed to find out the ratio of CGE through measuring the grain length of rice before and after cooking. In this study, the SNP marker system was not effective for identifying the CGE trait, contrast to success of previous research showing the SNP system co-segregate to 99% with many different rice varieties. While results of SSR marker assay was incompatible with the conventional method, which showed that the usage of SSR markers was incompletely efficient for detecting the CGE trait in rice. However, the data of this study will be useful for further research in selecting available marker for the identification of rice cooked grain elongation.